Invasive orchids: weeds we hate to love? - Ackerman, James (Universidad de Costa Rica, 2015)
Rare species that show habitat specificity and an aversion to habitat disturbance may be common in the Orchidaceae (Tremblay et al. 1998; Bergman et al. 2006). Nonetheless, most orchids may not be in such a critical state and many are, quite frankly, weedy. We may learn much about rare species by asking what makes other orchids common and resilient or actually dependent on change. Most orchids do occur in ephemeral or frequently dis- turbed habitats (Ackerman 1983; Catling 1996) whether they are pastures, roadsides, citrus groves, coffee and tea farms, or simply as epiphytes whose substrates, by definition, are temporary and run the gamut from durable tree trunks to short-lived twigs (Johansson 1974).